Intelligent biofilm with blueberry extract, rice straw nanocellulose and polyvinyl alcohol: Characterization and its application in visual freshness monitoring in tilapia fillets (Scientia Agropecuaria, 2025)
Intelligent packaging represents a sustainable solution for food preservation by enabling the monitoring of freshness through chromatic changes. In this study, a biofilm based on polyvinyl alcohol (PVA), nanocellulose (NC) extracted from rice straw and blueberry extract was developed and evaluated for its performance as a visual freshness indicator in tilapia fillets. Nanocellulose, obtained by TEMPO oxidation, exhibited proper integration into the polymeric matrix according to transmission electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis and X-ray diffraction analysis. The biofilms improved their mechanical properties with the addition of NC, by increasing tensile strength and reducing water solubility. However, the incorporation of anthocyanins increased solubility and water vapor permeability due to their hydrophilic character. Despite this, their high chromatic sensitivity to pH allowed for color changes: red in acidic media (pH 2-4) and green/brown in alkaline media (pH > 9). These visual changes validate the potential of anthocyanins as freshness indicators, positioning biofilms as a functional and sustainable alternative to conventional packaging. In addition to enabling real-time monitoring, these biofilms can contribute to reducing food waste and fostering more sustainable solutions in the packaging industry, with significant potential for innovative commercial applications.
Keywords: Vaccinium corymbosum; nanotechnology; thermal degradation; mechanical properties; pH indicator; sustainability